Overview of intoxications associated with the use of medicines registered in Brazil (Research, Society and Development, 2020)
Exogenous intoxication is characterized by the interaction of chemical substances with the living organism. Annually 1.5 to 3% of the population is intoxicated making the disease a public / collective health issue. Quantify and analyze reported cases of drug poisoning in Brazil. This was a documentary, retrospective, descriptive research with a quantitative approach. The notified cases of drug intoxication were collected from the Department of Informatics of the Unified Health System (DATASUS) having the variables studied: region, year, sex, circumstance, final classification and evolution. 224,901 cases of drug poisoning were studied in the aforementioned period, and through these cases it was found that there was a gradual increase in the number of notifications over the years studied, 28% in 2017. Of the notified cases 51% belonged the southeast region. The female sex was predominant, accounting for 70% of cases. The most reported circumstance of intoxication was suicide attempt (59%) and the final predominant classification was confirmed intoxication (68%). Considering the evolution of reported cases, most of them evolved to cure without sequelae (83%). The investigation made it possible to know the epidemiological profile of notified cases of drug poisoning in Brazil. From these findings, it is concluded that there is a need to implement policies to minimize the risks to human health due to the use of medicines. In addition, it is also important to incorporate the standard as a basic work tool to generate accurate and updated data in the national databases. Such factors demonstrate the importance of implementing a Toxicological Information and Assistance Center (CIAT) throughout Brazil, as well as Hospital Epidemiology Centers (NEH) to better monitor the profile of drug poisoning.